(untitled) (Colombia Medica, 1990)
Newborn children with congenital dysplasia of the hip are everywhere frequently misdiagnosed. Mistakes are common because a) clinical examination is designed to find useless signs with no diagnostic value, and b) hip flexibility has been investigated with inappropriate techniques. Therefore, a variation of the common examination method for congenital dysplasia of the hip is being proposed and described in this paper. The new technique, a modification of Ortolani’s and Barlow’s maneuvers, is useful for early diagnosis of congenital hip dysplasia among newborn children and infants several months of age. Traditional methods (Ortalani’s and Barlow’s maneuvers) and the new examination variation were assessed to find congenital hip dysplasia in two groups of newborn children. This trial succesfully demonstrates the clinical effectiveness of the new technique in the early detection of the disease.